Free radical behaviours during methylene blue degradation in the Fe2+/H2O2 system. Issue 9 (16th April 2019) - Wang, Zhonghua; Zhao, Haiqian; Qi, Hanbing; Liu, Xiaoyan; Liu, Yang
ABSTRACT: Behaviours of the free radicals during the methylene blue (MB) oxidation process in the Fe 2+ /H2 O2 system were studied to reveal the reason for the low utilization efficiency of H2 O2 . The roles ofO 2 − ∙, ∙ OH andHO 2 ∙ radicals were proven to be different in the MB oxidation process. The results showed thatO 2 − ∙ radicals had a strong ability to oxidize MB; however, they were not the main active substances for MB degradation due to the low concentration in the traditional Fe 2+ /H2 O2 system.HO 2 ∙ radicals could not oxidize MB. ∙ OH radicals were the main active substances for MB oxidation. In the short initial stage, the utilization efficiency of H2 O2 was high, because the generation rate of ∙ OH was much higher than that ofHO 2 ∙ . More ∙ OH radicals were involved in the MB oxidation reaction. In the long deceleration stage (after the short initial stage), a large amount of H2 O2 was consumed, but the amount of oxidized MB was very small. Most of the ∙ OH radicals were consumed via the rapid useless reaction between ∙ OH andHO 2 ∙ in this stage, resulting in the serious useless consumption of H2 O2 . It is a feasible method to improve the utilization efficiency of H2 O2 by adding suitable additives into the Fe 2+ /H2 O2 system to weaken the useless reaction between ∙ OH andHO 2 ∙ .